Persepsi Masyarakat terhadap Kota Lama sebagai Ruang Publik Budaya di Kota Semarang - Atia, Syarifah; Muafiq, Muhammad Miftakhul (Badan Riset dan Inovasi Daerah Kota Semarang, 2024)
Urban spatial planning cannot be separated from the elements of public open space. The city of Semarang has several public spaces that are often visited by the public, one of which is the Kota Lama Tourist Area. The development of the area into a public open space has caused the Old City of Semarang to experience spatial and non-spatial changes, including the value of the existing space. As one of the public spaces visited by tourists, the perception of tourists as users of the area is important to identify as one of the goals for formulating the policies needed to develop the Old City as a Cultural Public Space based on public perception. This research uses positivistic quantitative deductive methods and descriptive analysis and comparative analysis techniques. Descriptive analysis was carried out on the results of questionnaire data collection by weighting Likert scale scores. Based on studies that have been carried out, the condition of the Old City as a cultural public space is already in good condition. This is proven by the results of the community questionnaire, which predominantly said they agreed with several variables that determine the condition of the Old City of Semarang. There are main problems in the Old City as a public space, including the noise emitted from vehicles around the Old City, the existence and condition of inadequate hand washing facilities and the undirected circulation of vehicles around the Old City of Semarang.